Dinamika Kepribadian Menurut Teori Sigmund Freud: Analisis Psikologi Sastra pada Tokoh Restu dalam Novel 'Secret Obsession' karya Anggarani - Alvian Rahmad IlhamPermadi; Pradipa Juan Reswara; Eva Dwi Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is that the researcher wants to know intimately about the personality structure of the Id, Ego, Superego of the character Restu in the novel entitled